(untitled) (World Bulletin of Management and Law, 2025)
This article analyzes the current state of the procedure and criteria for assessing the effectiveness of family judges’ activities by properly organizing the activities of family judges operating in the Republic of Uzbekistan, the relevance of their improvement, and the proposals for introducing new criteria for organizing the activities of family judges and assessing the effectiveness of their activities, based on the experience of organizing the activities of family judges in foreign countries, in particular Japan, and their relevance.